Charles Erickson feeds the folding machine in the bindery room (1952)
News photo caption: "C.H. Gregory, instructor in Cal Poly's department of Printing, looks on as Charles Erickson feeds the folding machine in the bindery room. From left to right: Erickson; Gergery[sic]; Gerald Sherwin and Alfred Baima. The printing exhibit is one of the many shown at the annual 'county fair on a college campus' April 25-26." C. Herold Gregory (2nd from left)